Montessori Practical Life Activities and Early Childhood Independence: A Behaviorist and Constructivist Analysis - Asri Ulfah Wulan Sari; Siti Irene Astuti Dwiningrum (Assyfa Learning Journal, 2026)
Early childhood independence remains a persistent challenge in early education, as young children frequently exhibit high dependency on adults during routine daily activities due to an overemphasis on academic drills over practical life skills. This study aims to analyze the implementation of the Montessori Practical Life method in stimulating early childhood independence while critically examining its underlying mechanisms through behaviorist and constructivist learning theories. Utilizing a qualitative library research design, relevant academic literature published between 2021 and 2025 was gathered and analyzed using thematic content analysis. The findings reveal that structured, concrete, and repetitive practical life activities—spanning self-care, environmental maintenance, and social etiquette—significantly improve children's functional independence, motor coordination, discipline, and executive functioning. From a behaviorist lens, independent behaviors are cultivated through habituation, stimulus-response conditioning, and positive reinforcement. Concurrently, from a constructivist perspective, children actively construct personal autonomy, self-regulation, and conceptual understanding through direct, hands-on interaction with child-sized materials. In conclusion, combining behaviorist and constructivist paradigms proves that the Montessori Practical Life approach functions not merely as routine physical practice, but as a robust pedagogical framework that fosters sustainable self-reliance, character development, and holistic school readiness in early childhood education.